Curriculum Innovation for Children with Special Needs as an Effort to Increase Spiritual Intelligence - Anita Puji Astutik; Nadhirah Nordin; Isna Meilinda; Aulia Rahma (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
The curriculum used for children with special needs (CSN) has not yet been fully aligned with their characteristics, interests, and developmental needs, thus it has not been able to optimally enhance their spiritual intelligence. The purpose of this study is to develop an adaptive and contextual Islamic curriculum innovation as an effort to improve the spiritual intelligence of children with special needs. The research subjects were CSN students at Lentera Fajar Indonesia, an inclusive educational institution with diverse conditions including ADHD, sensory impairments, speech disorders, and mental retardation. The research method employed was Research and Development (R&D) using the ADDIE model, while data collection techniques included observation, interviews, and documentation, as well as pretest and posttest assessments. Data analysis was conducted using validity tests and paired sample t-tests to determine the significance of the curriculum development’s influence on the spiritual intelligence of CSN. The results showed that the developed curriculum was categorized as fairly valid with a percentage of 51–75% and was proven to have a significant impact on improving the spiritual intelligence of children, as evidenced by a significance value of 0.000 < 0.05. These findings indicate that curriculum development has a significant influence on enhancing the spiritual intelligence of children with special needs.